Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10290-006-0090-8
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative and Non-Cooperative R&D Policy in an Economic Union

Abstract: © Dette eksemplar er fremstilt etter avtale med KOPINOR, Stenergate 1, 0050 Oslo. Ytterligere eksemplarfremstilling uten avtale og i strid med åndsverkloven er straffbart og kan medføre erstatningsansvar. 6,6 &(175( ) 25 ,17(51$7,21$/ (&2120,&6 $1' 6+,33,1* SIØS -Centre for international economics and shipping -is a joint centre for The Norwegian School of Economics and Business Administration (NHH) and Institute for Research in Economics and Business Administration (SNF). The centre is responsible for researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…The symmetric game of Haaland and Kind (2006), and to a lesser extent their 2004 working paper, is, as far as we know, the analysis in the literature closest to that of the present article in that they have R&D subsidies in a full international intra‐industry trade model, that consumers in both countries buy the output of both firms. Many of the formal assumptions of the present article are similar to the symmetric model of Haaland and Kind (2006) as well: improvements in quality shift out the demand function, the cost of quality function is quadratic and independent of quantity, and consumer surplus is included in social surplus. Their asymmetric model differs significantly from our asymmetric model in that they do not consider bidirectional intra‐industry trade.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The symmetric game of Haaland and Kind (2006), and to a lesser extent their 2004 working paper, is, as far as we know, the analysis in the literature closest to that of the present article in that they have R&D subsidies in a full international intra‐industry trade model, that consumers in both countries buy the output of both firms. Many of the formal assumptions of the present article are similar to the symmetric model of Haaland and Kind (2006) as well: improvements in quality shift out the demand function, the cost of quality function is quadratic and independent of quantity, and consumer surplus is included in social surplus. Their asymmetric model differs significantly from our asymmetric model in that they do not consider bidirectional intra‐industry trade.…”
Section: Introductionmentioning
confidence: 82%
“…We suspect that the reason may be their firms play a one‐stage game where quality is a tactical variable, while ours play a two‐stage game where quality is a strategic variable. In any event, formally, Haaland and Kind (2006) give policymakers no guidance on the question of whether R&D subsidies are corporate welfare. More invidiously, if a policymaker thinks that raising profit is corporate welfare, regardless of the effect on social surplus, then Haaland and Kind’s analysis would lead the policymaker to precisely the wrong conclusion, namely, that all R&D subsidies are corporate welfare.…”
Section: Introductionmentioning
confidence: 99%
“…It affirmed the importance of a proper R&D policy for rent shifting of firms. On such a basis, Haaland and Kind (2006) have elaborated on the implications of cooperative and non-cooperative R&D strategies, and indicated that the optimal R&D policy should consider the consumer-surplus effects and producer-stealing effects of R&D under the market with imperfect competition. Haaland and Kind (2008) further indicated that coordinated strategy harmonization eliminates policy competition, but it is not necessary to ensure welfare maximization.…”
Section: Introductionmentioning
confidence: 99%
“…The formal assumptions of the paper follow those of Gretz et al (2009), Haaland and Kind (2006), and DeCourcy (2005. A two-country two-firm intra-industry trade model is used; the formal game has three stages: first, governments announce their policies, then firms decide their R&D spending, and finally Cournot-quantities are determined.…”
mentioning
confidence: 99%